2019
DOI: 10.1016/j.hal.2019.101671
|View full text |Cite
|
Sign up to set email alerts
|

Growth and epiphytic behavior of three Gambierdiscus species (Dinophyceae) associated with various macroalgal substrates

Abstract: demonstrated in this study, could help to better inform efforts of sampling and monitoring of this benthic toxic dinoflagellate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A study of the growth and epiphytic behaviour of three Gambierdiscus species, G. balechii, G. caribaeus Vandersea, Litaker, M.A.Faust, Kibler, W.C.Holland, & P.A.Tester, and a new Gambierdiscus ribotype, type 7, supported the contention that there are no specific preferences for macroalgal host species and that other environmental factors, such as light avoidance, may be at play [47]. Further research is needed to identify environmental factors that influence macroalgae composition and distribution, and thus, an increased risk of CFP [48].…”
Section: Macroalgae Substratesmentioning
confidence: 89%
“…A study of the growth and epiphytic behaviour of three Gambierdiscus species, G. balechii, G. caribaeus Vandersea, Litaker, M.A.Faust, Kibler, W.C.Holland, & P.A.Tester, and a new Gambierdiscus ribotype, type 7, supported the contention that there are no specific preferences for macroalgal host species and that other environmental factors, such as light avoidance, may be at play [47]. Further research is needed to identify environmental factors that influence macroalgae composition and distribution, and thus, an increased risk of CFP [48].…”
Section: Macroalgae Substratesmentioning
confidence: 89%
“…Although, beyond this study, to differentiate, there are multiple aspects where macroalgal abundance and composition might impact Gambierdiscus abundance and ciguatoxin transferability. Specifically, Gambierdiscus-macroalgae host interactions, which can be species-specific, might depend on shading potential, chemical cues, and hostpalatability to higher trophic levels [58][59][60]. Since Gambierdiscus species determination has further developed since this study, future studies could determine if there are particular in situ host associations or macroalgal abundance that favor particularly toxic species/strains and if these associations are linked to the environmental conditions and benthic community compositions that vary between these nearshore and offshore sites.…”
Section: Nearshore Vs Offshore Sitesmentioning
confidence: 99%
“…Growth is dependent on many interacting environmental factors including temperature, light, and nutrients, all of which can vary with depth and aspect on the reef. Mustapa et al [ 270 ] reported growth rates for Malaysian Gambierdiscus isolates growing in culture on turf algae that ranged between ~0.1 to <0.3 divisions/day. Growth rates of 0.1–0.25 divisions/day (i.e., population doubling every 4–10 days) could possibly maintain a Gambierdiscus population on turf algae if, as suggested by Marshell and Mumby [ 263 ] and references therein, that turf algae biomass can be turned over by grazers every 4 to 25 days (especially as reported growth rates for Gambierdiscus are often from experiments trying to produce optimal laboratory growth conditions).…”
Section: A Conceptual Model For Ciguateric Food-chains On the Great Barrier Reefmentioning
confidence: 99%